The impact of continuous training on a firm's innovations - Stefan Bauernschuster; Oliver Falck; Stephan Heblich (Center for Economic Studies and ifo Institute (CESifo), 2008)
Keeping up with rapid technological change necessitates constant innovation. Successful innovation depends on both incumbent workers' knowledge, based on experience, and knowledge about the latest technologies, along with the skills needed to implement them. Both of these knowledge-based elements of innovation can be attained through moderate labor force turnover in combination with continuous training. Based on German micro data, we find empirical evidence in support of training leading to innovation within a multivariate regression framework. However, when instrumenting training by the existence of a union's contract or a works council this impact disappears.
Keywords: J24; L11; O31; 330; innovation; training; unions; works councils; Innovation; Betriebliche Weiterbildung; Betriebliche Bildungsarbeit; Mitbestimmung; Deutschland